Study on Steel Fibre Reinforced Self Compacting Concrete - Venkateshwaran, A.; Nandhini, K.; Ponmalar, V. (Asian Journal of Engineering and Applied Technology, 2018)
Self Compacting Concrete (SCC) consists of a higher amount of fine content and admixtures, thus eliminating the time for compaction and labour cost. Micro silica is a by-product of the industrial manufacture of ferrosilicon and metallic silicon that is been made in high-temperature electric arc furnace. The ferrosilicon is drawn from 2000°C furnace, thus after when it cools down, the particles are condensed and are trapped in huge cloth bags. The condensed fume is processed by removing impurities and thus micro silica is being formed. Micro silica, as a waste by-product, being used for land filling, instead it can be used as an additive to concrete. The overall weight of the concrete increases up to 15 percent, thus increasing the unit weight of concrete. In addition, nano silica and steel fibres have been used to improve the strength and durability of concrete. Addition of silica to a concrete mix alters the cement paste structure. The resulting paste contains more of the calcium-silicate hydrates and less of the easily soluble calcium hydroxides. Due to its smaller size particle distribution, they disperse among and separate the cement particles. In the present study, different mix ratio using micro silica, nano silica and steel fibres has been prepared to study the fresh and hardened properties of SCC respectively.